EFEK PEMBERIAN BUAH PISANG PADA PENURUNAN KELELAHAN KERJA BAGI PEKERJA DI BAGIAN PELINTINGAN ROKOK - Mashuri, Yusuf Ari; Sweetry, Zara Offia; Sjarifah, Ipop (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Manual rolling work can cause work fatigue due to high job targets. Banana (Musa sapientum) contains natural sugars such as sucrose, fructose, and glucose as a source of energy. Work fatigue can be overcome with energy supplementation such as banana. This study aimed to determine the effect of banana supplementation on the level of work fatigue of cigarette manual rolling workers in X factory Karanganyar. This research was a quasi-experimental, with a one-shot case study design. The sampling technique used was simple random sampling, A total of 54 workers was randomly recruited as the sample. The independent variable of this study was banana (Musa sapientum), while the dependent variable was work fatigue. The Wilcoxon test was used to analyze the data. The Wilcoxon test showed that there was a significant difference between work fatigue before and after the banana supplementation to the cigarette manual rolling worker of X factory Karanganyar (p-value = 0.000). Thus, Banana (Musa sapientum) can be given as a food supplement to overcome the work fatigue problems in manual rolling workers.